2017
DOI: 10.21147/j.issn.1000-9604.2017.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different lymph node staging systems in prognosis of gastric cancer: a bi-institutional study from Hungary

Abstract: ObjectiveThe Union for International Cancer Control (UICC) Node (N) classification is the most common used staging method for the prognosis of gastric cancer. It demands adequate, at least 16 lymph nodes (LNs) to be dissected; therefore different staging systems were invented.MethodsBetween March 2005 and March 2010, 164 patients were evaluated at the Department of General Surgery in the Kenézy Gyula Hospital and at the Department of General, Thoracic and Vascular Surgery in the Kaposi Mór Hospital. The 6th, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Nodal involvement signi cantly affected the prognosis of GC patients because it is the major root of tumor relapse after surgery [13,14]. Thus, standardized lymph nodes dissection is the basic requirement for curative (R0) gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Nodal involvement signi cantly affected the prognosis of GC patients because it is the major root of tumor relapse after surgery [13,14]. Thus, standardized lymph nodes dissection is the basic requirement for curative (R0) gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Nodal involvement significantly affected the prognosis of GC patients because it is the major root of tumor relapse after surgery [14,15]. Thus, standardized lymph nodes dissection is the basic requirement for curative (R0) gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A noteworthy difference in the 8th edition system involves separate consideration of N3a and N3b in the TNM staging system, which has been demonstrated to achieve improved prognosis prediction in patients with stage III gastric cancer (5,6). A number of previous studies have indicated that the MLR is an improved method for evaluating the prognosis of patients with gastric cancer compared with the previous TNM staging system (18,19). In addition, the LODDS staging system has been demonstrated to be superior in terms of accuracy compared with the MLR and TNM systems with regard to Table III.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study concluded that LODDS was the superior staging system. Tóth et al (19) revealed that the LODDS staging system was the best predictor of prognosis when <16 LNs were retrieved and the MLR should be applied in patients who underwent extended lymphadenectomies. Aurello et al (23) analyzed 177 patients and identified that the LODDS staging system, nodal ratio and pN are all prognostic factors based on multivariate analysis, and the LODDS staging system was capable of predicting survival According to mixed analysis of the five groups, the 5-year survival rate was 84.6% for T1, 72.3% for T2, 44.7% for T3, 37.9% for T4a and 27.3% for T4b.…”
Section: Univariate Multivariate Analysis Analysis ------------------mentioning
confidence: 99%
See 1 more Smart Citation